A Survey of multi-criteria decision-making in e-banking websites quality evaluation - Adepoju, Solomon Adelowo; Alhassan, John Kolo; Ojerinde, Oluwaseun Adeniyi; Shaba, Christy Dayida (Penerbit Universiti Kebangsaan Malaysia, 2024)
Electronic banking grants users access to banking services virtually and offers convenience, ease of use, low cost, time saving, fast delivery and online bill payment. These services are mostly provided through websites; hence evalution of its quality and services are very important. Website quality evaluation entails numerous dimensions and attributes and the processes which are critical as well as complex requires quality, accuracy and objectivity. This paper surveys the criteria and methodologies that have been used over years in e-banking websites quality as well as e-services quality evaluation. The survey covers articles within a five-year period from 2018 – 2022 which mostly focus on e-banking websites quality evaluation. Twenty-three articles which met the inclusion and exclusion criterai set by the authors are used for the study. Results show that the everage number of crtieria used in most studies are six with security, privacy and ease-of-use taking the lead as the mostly used criteris across different studies. Also, various types of multi-criteria decision-making model were used by diffferent and there is none that is dominant among them. It was observed that fuzzy type of the various types of multi-criteria decision-making models are mostly used in many studies. In general, studies with focus on e-banking websites quality are not yet given much attention in the literature.